2019
DOI: 10.1371/journal.pone.0211381
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic (MD) studies on Gln233Arg (rs1137101) polymorphism of leptin receptor gene and associated variations in the anthropometric and metabolic profiles of Saudi women

Abstract: The Gln233Arg (A>G; rs1137101) polymorphism of the leptin receptor gene (LEPR) has been investigated extensively and is reported to be associated with different metabolic states. In this investigation, we aimed to study the frequency of Gln233Arg genotypes and alleles in a group of Saudi women stratified by their body mass index (BMI), to correlate the LEPR genotypes with variations in anthropometric, lipid and hormonal parameters and to investigate conformational and structural variations in the mutant LEPR u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
1
17
0
4
Order By: Relevance
“…Evidence suggests that the resulting conformational changes of the protein influence the LEPR functions and could lead to an abnormal downstream signaling pathway of JAK2 due to a leptin receptor deficiency. The consequences of these abnormalities are leptin resistance and, therefore, an attenuated leptin signaling [23]. Accordingly, it would result in a more significant presence of obesity by Q223R genotype, as we have seen in this study, as well as in previous researches in both pediatric [24,25] and adulthood populations [26][27][28].…”
Section: Discussionsupporting
confidence: 72%
“…Evidence suggests that the resulting conformational changes of the protein influence the LEPR functions and could lead to an abnormal downstream signaling pathway of JAK2 due to a leptin receptor deficiency. The consequences of these abnormalities are leptin resistance and, therefore, an attenuated leptin signaling [23]. Accordingly, it would result in a more significant presence of obesity by Q223R genotype, as we have seen in this study, as well as in previous researches in both pediatric [24,25] and adulthood populations [26][27][28].…”
Section: Discussionsupporting
confidence: 72%
“…Authors argue that the cause of obesity is not the defects in leptin, but that the problem lies in the resistance to leptin. Leptin resistance can occur due to defects in the gene itself (polymorphism, lipoprotection, voltage of the endoplasmic reticulum), as well as post receptor defect in hormone action (inflammatory reactions), which may interfere with intracellular transport of messages (Lopez et al, 2016;Daghestani et al, 2019). In this study we also have proved that in pregnant women with LEPR Gln223Arg gene GG-polymorphism, excessive serum hyperleptinemia is based on leptin resistance due to modified transcriptional activity of the LEPR gene.…”
Section: Discussionmentioning
confidence: 53%
“…However, when we carried out, in our Mediterranean population, a whole gene screening to capture a more complete set of SNPs in the same candidate genes (LEP, SLC32A, GCKR, CCNL1, COBLL1, and FTO), we did obtain several statistically significant association between other SNPs in these genes and plasma leptin concentrations. In addition to those genes, we included the LEPR gene that, although not showing up as relevant in the GWAS de Kilpeläin et al [37], has been reported in other studies as having significant associations of SNPs in the LEPR gene with circulating leptin levels [24,26,33,74]. In the LEPR screening, we also found several SNPs showing statistically significant associations with leptin levels in our population.…”
Section: Discussionmentioning
confidence: 76%